Variability in the dolphin kick under four conditions - Barthels, K. M.; Adrian, A. J. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
It was the purpose of this investigation to identify differences and similarities in selected joint movements of dolphin kick patterns under four conditions. A secondary purpose was to identify the degree to which selected muscles functioned during each condition.